2013
DOI: 10.1155/2013/963930
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Diabetic and Nondiabetic Patients Undergoing General and Vascular Surgery

Abstract: Aims. Preoperative diabetic and glycemic screening may or may not be cost effective. Although hyperglycemia is known to compromise surgical outcomes, the effect of a diabetic diagnosis on outcomes is poorly known. We examine the effect of diabetes on outcomes for general and vascular surgery patients. Methods. Data were collected from the Michigan Surgical Quality Collaborative for general or vascular surgery patients who had diabetes. Primary and secondary outcomes were 30-day mortality and 30-day overall mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Umpierrez et al found that incident hyperglycemia was a better predictor of IHM than a prior history of diabetes, concluding that hyperglycemia and not diabetes itself increased the risk of death [31]. Serio et al (2013) investigated the postoperative risk of morbidity and mortality in diabetic patients versus nondiabetic patients who underwent general or vascular surgery and found that the presence of diabetes was not predictive of mortality; however, vascular surgery itself was predictive of mortality [32]. Perhaps the fact that subjects suffering diabetes were more likely to be admitted to the hospital for less severe illnesses might explain this association.…”
Section: Discussionmentioning
confidence: 99%
“…Umpierrez et al found that incident hyperglycemia was a better predictor of IHM than a prior history of diabetes, concluding that hyperglycemia and not diabetes itself increased the risk of death [31]. Serio et al (2013) investigated the postoperative risk of morbidity and mortality in diabetic patients versus nondiabetic patients who underwent general or vascular surgery and found that the presence of diabetes was not predictive of mortality; however, vascular surgery itself was predictive of mortality [32]. Perhaps the fact that subjects suffering diabetes were more likely to be admitted to the hospital for less severe illnesses might explain this association.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of insulin therapy is to avoid surgical wound complications,92 gastrointestinal function and inflammatory responses 70. Every 40 mg/dl increase in glucose levels increases the risk for graft failure and infection by 30%, followed by a longer intensive care unit (ICU) stay 93. Increased glucose tolerance, diagnosed by fasting glucose levels and OGTT (oral glucose tolerance test) resulted in a significantly higher risk for developing postoperative cardiovascular events (myocardial infarction, angina pectoris, transient ischemic attacks or cerebrovascular occlusions), compared to diabetic patients, showing non-significant risk-increase 94…”
Section: Discussionmentioning
confidence: 99%
“…Study from Krinsley et al showed that the mortality is twice as high when glucose level is above 140–150 mg/dl ( 41 ). An increase of glucose level for every 40 mg/dl carries a 30% higher risk of infection, graft failure, and longer ICU stay ( 42 ). Achieving these values is significant for wound healing, integrity of gastrointestinal system, and inflammatory response reduction ( 43 ).…”
Section: Guidelines For Management In Postoperative Periodmentioning
confidence: 99%